Health universalism in Argentina between 2003 and 2015: assessments and challenges based in a macro-institutional approach - Magdalena Chiara; María Crojethovic; Ana Ariovich (Instituto de Salud Colectiva, Universidad Nacional de Lanús, 2017)
Debates about universalism in health have been gaining ground in Latin America and have entered the policy agenda with differing results. Notwithstanding the country's federalism, the most profound changes that took place in Argentina in the last decade occurred in the arena of national politics. Based on the theoretical contributions of historical neo-institutionalism and implementation studies, this paper aims to analyze, from a macro institutional approach, the scope of the national policy regarding health universalization. This descriptive study is based on secondary sources and the review of research results on the implementation of the programs Remediar, Sumar and Plan Nacer in relation to four variables: coverage, access, sets of benefits and rights included in the policy. Given the characteristics of the Argentine institutional matrix, program implementation in subnational scenarios can be expected to confront complex and heterogeneous terrain in which the programs acquire new meanings with respect to the goal of universality that each poses.